Raspberry Pi projects for kids: start your own coding adventure with your kids by creating cool and exciting games and applications on the Raspberry Pi - Bates, Daniel (Community experience distilled., 2014)
Technology today is growing rapidly, with all sorts of cool gadgets, applications, and games made thanks to the rise of computer programming. The Raspberry Pi is a crafty device that has promoted the teaching of basic computer science in schools, catching the attention of both young and old. Although learning to program offers a unique set of skills that allows you to explore your creative side, it has its own challenges, which may mean you will need a helping hand. This handy guide will launch you into the world of computer programming by showing you how to build your own amazing applications. Raspberry Pi Projects for Kids contains several awesome projects for you to get hands-on with, including creating your own games, crafting your own simple electronics, and making your own interactive map. By learning how to use Scratch and Python in your programming, you will be a computer scientist in no time! After you have become comfortable with setting up and playing with your Raspberry Pi, you will be transported into this exciting world of technology, where you will get to grips with using Scratch, Raspberry Pi’s official programming language, in order to develop your own version of Angry Birds! After connecting new circuitry, lights, and switches to your Raspberry Pi, you will then get to use Scratch to create your own reaction game. See for yourself who’s the quickest off the mark!)You will finally get to step things up by developing an interactive map of your own hometown using the Python programming language. You will be working for Google before you know it! This book will teach you everything you need to know about using your Raspberry Pi in order to develop your own games, applications, and electronic circuits. It’s time to have your Pi and eat it, because you will be able to create virtually anything you like.